In Vivo Osteogenesis and In Vitro Streptococcus mutans Adherence: Porous-Surfaced Cylindrical Implants vs Rough-Surfaced Threaded Implants - Prado, Renata Falchete do; Oliveira de Vasconcellos, Luis Gustavo [UNESP]; Reis de Vasconcellos, Luana Marotta [UNESP]; Alves Cairo, Carlos Alberto; Leite, Daniel de Oliveira [UNESP]; Santos, Alessandra dos [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Romeiro, Rogerio de Lima; Balducci, Ivan [UNESP]; Carvalho, Yasmin Rodarte [UNESP] (Quintessence Publishing Co Inc, 2013)
Purpose: To analyze and compare bone apposition at the interface of commercially available rough-surfaced, threaded implants with porous-surfaced, cylindrical implants after several healing periods in a rabbit model. In addition, the study aimed to elucidate the influence of the implant surface configuration on Streptococcus mutans adherence. Materials and Methods: Using a powder metallurgy technique, a new method was developed to produce titanium implants with a dense core and porous surface to increase bone-implant contact (BIC). Sixty implants were placed in 15 rabbits. In each rabbit, two experimental and two control implants were placed in the right or left tibia. The experimental implants were inserted under pressure into the surgical cavity, while the control implants were self-threaded. The rabbits were euthanized at 4, 8, and 12 weeks post-insertion for undecalcified histologic processing and morphometric evaluation of BIC. Additionally, 16 implants, eight experimental and eight control, were incubated with S mutans to evaluate adherence for each type of implant. Analysis of variance with repeated measures and the Student t test were applied, respectively. Results: Histology showed intimate bone-implant interfaces without soft tissue intervention in both groups. Porous-surfaced cylindrical implants showed a higher BIC (72.41% +/- 9.47%) than the rough-surfaced screw implants (61.23% +/- 14.12%) (P = .013), while no significant difference in S mutans adherence occurred (P = .351). The implant type effect was more pronounced in the 4-week healing period groups (P = .029). The percentage of BIC was similar throughout the healing periods (P = .333), but gradually increased over time. Conclusion: Within the limitations of this study, the results suggest that the new implant design increased BIC without provoking greater S mutans adherence.
Keywords: bacterial adherence; bone ingrowth; implant design; porous titanium; surface